Penyuluhan Gizi Seimbang Pada Ibu Hamil di Posyandu Prima Desa Congkrang Kecamatan Muntilan Kabupaten Magelang - Eniyati, Eniyati; Lutfiyati, Afi; Fitria A, Ika; Yulaikhah, Lily (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
The pregnancy period requires special attention because it is an important period in the 1,000 days of life. Pregnant women are one of the groups that are prone to malnutrition. Nutritional intake of pregnant women has a great effect on fetal growth. Good nutritional status in pregnant women can prevent Low Birth Weight (BBLR) and stunting (short). One of the factors that affect stunting is the genetics of parents, namely the height and weight of the parents. The risk of the child experiencing stunting is higher if the mother is <150 cm tall. Short mothers have the possibility of giving birth to short babies as well. The nutritional status of the mother before and during pregnancy can affect the growth of the fetus that is being conceived (Ministry of Health of the Republic of Indonesia, 2019). A pregnant woman must have a good nutritional status and consume a variety of foods in both proportions and amounts. Balanced nutrition is the arrangement of daily food that contains nutrients in the type and amount that suits the body's needs, paying attention to the principles of food diversity or variation, physical activity, hygiene and ideal body weight. Based on the description above, it can be identified that nutritional status is very important for pregnant women. The results of previous community service were obtained that out of 14 pregnant women, there were 8 pregnant women with abnormal nutritional status. Some pregnant women still have a LILA less than normal, which is less than 23.5 cm. And some pregnant women have abnormal BMIs. Given the importance of balanced nutrition in pregnant women, community service will be carried out by providing counseling. The results of this service were from a total of 11 pregnant women (100%) with a healthy reproductive age, which was between 20 to 35 years. The obstetric status of pregnant women is mostly multipara, a total of 9 pregnant women (82%) are multigravida. Nutritional status based on the Body Mass Index (BMI) of the majority with overweight as many as 9 pregnant women (82%) and 1 pregnant woman (0.09%) is normal while 1 pregnant woman (0.09%) is underweight. Based on the test scores before and after being given counseling, the results were obtained that there was a change in knowledge.